2023
DOI: 10.1080/21645515.2023.2189885
|View full text |Cite
|
Sign up to set email alerts
|

The Matrix-M™ adjuvant: A critical component of vaccines for the 21 st century

Abstract: Matrix-M™ adjuvant is a key component of several novel vaccine candidates. The Matrix-M adjuvant consists of two distinct fractions of saponins purified from the Quillaja saponaria Molina tree, combined with cholesterol and phospholipids to form 40-nm open cage-like nanoparticles, achieving potent adjuvanticity with a favorable safety profile. Matrix-M induces early activation of innate immune cells at the injection site and in the draining lymph nodes. This translates into improved magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 91 publications
(182 reference statements)
1
18
0
Order By: Relevance
“…falciparum . Two chimeric proteins (R0.6C and ProC6C) were formulated on aluminum hydroxide (Alhydrogel [AlOH] adjuvant) and evaluated with and without the saponin-based adjuvant Matrix-M ( 21 ). We found that both the ProC6C and R0.6C vaccines were well tolerated and induced IgG antibodies against the vaccine antigens and their respective constituent antigens.…”
Section: Discussionmentioning
confidence: 99%
“…falciparum . Two chimeric proteins (R0.6C and ProC6C) were formulated on aluminum hydroxide (Alhydrogel [AlOH] adjuvant) and evaluated with and without the saponin-based adjuvant Matrix-M ( 21 ). We found that both the ProC6C and R0.6C vaccines were well tolerated and induced IgG antibodies against the vaccine antigens and their respective constituent antigens.…”
Section: Discussionmentioning
confidence: 99%
“…ISCOM is formed as a result of the self‐assembly of a mixture of phospholipid, cholesterol and saponin under hydrophobic driving force (Figure 8B). [ 191 ] Saponin is a crude mixture of a collection of triterpene compounds extracted from in the South American soapbark tree Quillaja saponaria Molina , especially, its cortex. Saponin possesses a strong adjuvanticity, while in ISCOM it also plays an additional role in conferring the cage‐like structure to this special NP.…”
Section: The Innovative Subunit Vaccines and Translational Platformsmentioning
confidence: 99%
“…To enhance the immune response and stimulate high levels of neutralizing antibodies, NVX-CoV2373 is formulated with Novavax's patented saponin-based Matrix-Mt adjuvant. 126 This adjuvant has been extensively tested and has demonstrated a potent and well-tolerated effect by stimulating the entry of antigen-presenting cells into the injection site and enhancing antigen presentation in local lymph nodes, thereby boosting the immune response. This protein-based vaccine candidate is designed to teach the immune system how to recognize and fight the SARS-CoV-2 virus, providing protection against COVID-19.…”
Section: Benefits Of Adjuvants In Covid-19 Vaccinesmentioning
confidence: 99%
“…Other saponin-based adjuvants, such as QS-21, have been evaluated in clinical trials for cancer vaccines and infectious disease vaccines, and have shown to induce strong immune responses and improve vaccine efficacy. 126 However, their complex structure and variable composition may affect their consistency and reproducibility, and their potential toxicity and hemolytic activity need to be carefully evaluated in preclinical and clinical studies in dLNs. AS02, composing of MPL and QS-21, is undergoing phase 2 trial in a malaria vaccine.…”
Section: Clinical Trials and Licensing Of Vaccine Adjuvantsmentioning
confidence: 99%